2021
DOI: 10.1002/bit.27703
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy‐inducing peptide increases CHO cell monoclonal antibody production in batch and fed‐batch cultures

Abstract: The development of generic biopharmaceuticals is increasing the pressures for enhanced bioprocess productivity and yields. Autophagy (“self‐eating”) is a cellular process that allows cells to mitigate stresses such as nutrient deprivation. Reputed autophagy inhibitors have also been shown to increase autophagic flux under certain conditions, and enhance recombinant protein productivity in Chinese Hamster Ovary (CHO) cultures. Since peptides are commonly added to bioprocess culture media in hydrolysates, we eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…For the first time, lipidomics analysis has been performed for lipid identification and lipid quantitation in fed-batch culture (Ali et al 2018 ). In addition, feed composition has been linked with cell metabolism regulation to demonstrate fed-batch culture (Braasch et al 2021 ) (Fig. 1 ).…”
Section: Feed Composition In Fed-batch Culturementioning
confidence: 99%
See 1 more Smart Citation
“…For the first time, lipidomics analysis has been performed for lipid identification and lipid quantitation in fed-batch culture (Ali et al 2018 ). In addition, feed composition has been linked with cell metabolism regulation to demonstrate fed-batch culture (Braasch et al 2021 ) (Fig. 1 ).…”
Section: Feed Composition In Fed-batch Culturementioning
confidence: 99%
“…Autophagy-inducing peptide (AIP), a derivative of the autophagy protein Beclin 1, facilitated the production of mAbs in CHO cells by regulating cellular autophagy. The addition of 3 µM of AIP in fed-batch culture ameliorated the expression level of human IgG1, and IgG1 concentration exceeded 1200 µg/mL (Braasch et al 2021 ). The yield of Fc-fusion protein (Fc) in fed-batch culture raised twofold by Yeast hydrolysate (YE), and YE also increased CHO cells size and intracellular nucleotide content (Hu et al 2018 ).…”
Section: Other Componentsmentioning
confidence: 99%
“…On the other hand, by adding 3 µM autophagy‐inducing peptide in the serum‐free cultures, IgG concentration significantly improved by over 2-fold compared to the control cultures in Chinese Hamster Ovary (CHO) cells (Braasch et al . 2021 ). Treatment with the appropriate autophagy inducers such as rapamycin and everolimus increased the production of secreted antibody scFv-Fc in insect cells (Nakanuma et al .…”
Section: Resultsmentioning
confidence: 99%
“…Emerging evidence indicates that autophagy pathway regulates secretion of specific cargos instead of lysosomal degradation ( New and Thomas, 2019 ). Tat-BECN1 increases the release of insulin in murine and human primary islets ( Goginashvili et al, 2015 ) (Tat-BECN1 is also reported to reduce adenosine-stimulated insulin secretion in islets ( Israeli et al, 2018 )), the secretion of candidate protein biomarkers of tumor cell autophagy ( Kraya et al, 2015 ), and the production of monoclonal antibody in CHO cells ( Braasch et al, 2021 ). Tat-BECN1 restores collagen secretion from chondrocytes to extracellular matrix and rescues bone growth in mice with lysosomal storage disorders ( Bartolomeo et al, 2017 ) or mice with FGF signaling defects ( Cinque et al, 2015 ).…”
Section: Effects Of Tat-becn1 On Degradationmentioning
confidence: 99%
“…Among these autophagy activators, rapamycin is widely used in basic and translational research; it inactivates mechanistic target of rapamycin complex 1 (mTORC1), the nutrient-sensing kinase complex that promotes anabolism and inhibits catabolism, mainly autophagy (Saxton and Sabatini, 2017). However, specific (Sun et al, 2021) Rat, mouse, human iPSC-derived Cardiomyocytes Primary culture (Nah et al, 2020) Human Bone osteogenic sarcoma U2OS (Wang et al, 2018) African green monkey Kidney Vero-B4 (Gassen et al, 2019) Chinese hamster Ovary CHO (Braasch et al, 2021) Tissues in which Tat-BECN1-induced autophagy is experimentally validated Species Tissues References Mouse Heart (Shirakabe et al, 2016;An et al, 2017;Sun et al, 2018;Tong et al, 2019;Nah et al, 2020) Rat, mouse Brain (Li et al, 2016;He et al, 2017;Zhang et al, 2017;Luo et al, 2018;Shehata et al, 2018;Glatigny et al, 2019;He et al, 2019;De Risi et al, 2020;Forte et al, 2020;Kim et al, 2021) Mouse Spinal cord (He et al, 2016) Mouse Eye (Kasetti et al, 2021) (Continued on following page)…”
Section: Introductionmentioning
confidence: 99%